The Effect of Electronic Word of Mouth and Service Quality on Buying Interest at Mega Manna Hotel Bengkulu Selatan - Calvin Fransisco; Ratnawilli Ratnawilli (Journal of Indonesian Management, 2022)
This study aims to determine the effect of electronic word of mouth and service quality on purchase intention at Mega Manna Hotel Bengkulu Selatan, either partially or simultaneously. There are several independent variables (x) that will be discussed in this study, including Electronic Word Of Mouth and Service Quality. In this study, there are several data analysis techniques used, including using instrument tests, classical assumption tests, analysis of respondents' responses, multiple linear regression analysis, determinant coefficients, and also hypothesis testing. From the results of multiple linear regression, the regression equation is as follows: Y = 7.358 + 0.222 (X1) + 0.365 (X2). Based on the multiple linear regression equation above, it can be interpreted that: The constant value of 7358 means that if the Electronic Word Of Mouth (X1) and Service Quality (X2) variables are equal to zero, then the Purchase Interest variable (Y) remains. The X1 (Electronic Word Of Mouth) coefficient of 0.222 means that if the Electronic Word Of Mouth decreases by one unit, the Purchase Interest value will increase. Assuming that the Service Quality variable (X2) is considered constant or constant. The X2 coefficient (Quality of Service) of 0.365 means that if Service Quality increases by one unit, the value of Purchase Interest will increase. Assuming if the variable Electronic Word Of Mouth (X1) is considered constant or constant. From the results of the tests that have been carried out, it can be concluded that the Electronic Word Of Mouth and Service Quality variables have an effect partially or simultaneously on Purchase Interest at Mega Bengkulu Selatan Hotel